Islam: Agama Kemanusiaan - Zainuddin, M. (el Harakah: Jurnal Budaya Islam, 1999)
Islam provides the guidance of human life from the smallest problem to the greatest affairs, ranging from household affairs, sleep, eat and drink up to the affairs of the nation and state. This paper raises how Islam covers all aspects of life as a religion of humanity. If taken seriously in the verses of the Qur'an or as Sunnah, will undoubtedly be found, that the core of the teachings of Islam is faith and righteousness. Islam is more than a formal religion, but it is also a great treatise for social transformation and a challenge to personal interests. Islam is a humanism, a religion that is very concerned with humanity as a central goal. This is the basis of Islam. Therefore, the greatest task of Islam is actually to transform social and cultural transformation with Islamic values. Islam memberikan tuntunan hidup manusia dari persoalan yang paling kecil hingga ke urusan yang paling besar, mulai dari urusan rumah tangga, tidur, makan dan minum sampai pada urusan bangsa dan negara. Tulisan ini mengangkat bagaimana Islam mencakup segala aspek kehidupan sebagai agama kemanusiaan. Jika dicermati secara serius dalam ayat-ayat al Quran maupun as sunnah, niscaya akan ditemukan, bahwa inti ajaran Islam adalah iman dan amal saleh. Islam lebih dari sekedar sebuah agama formal, tetapi juga risalah yang agung bagi transformasi sosial dan tantangan bagi kepentingan-kepentingan pribadi. Islam adalah sebuah humanisme, yaitu agama yang sangat mementingkan manusia sebagai tujuan sentral. Inilah dasar Islam. Oleh karena itu, tugas terbesar Islam sesungguhnya adalah melakukan transformasi sosial dan budaya dengan nilai-nilai Islam.